Animated Cartoon Film Discussion: Role in Improving Speaking Skill - Indah Werdiningsih (EDUPEDIA, 2021)
This study aims to investigate how cartoon film based-discussion can improve students’ speaking. This Classroom Action Research was conducted at SMA Muhammadiyah 3 Jember. The subjects of the study were 22 female and 10 male students. The data were collected through English speaking test. From the test result, cartoon film based-discussion was very effective; there was a significant increase in student’s speaking skill (M=76.09 in Cycle 1 to M=77.28 in Cycle 2) and students’ active participation (76.56% - 79.68%). This leads to conclusion that cartoon film based-discussion can improve students’ speaking and active participation by three main factors; First, they can discuss about particular topics in the discussion before taking the Speaking test. Second, cartoon film succeeds to stimulate students’ mind in collecting vocabularies during watching. Third, students’ grammar and pronunciation are also increased because they are accustomed to the structure of English subtitle provided in the movie.